Genotype-specific prevalence of human papillomavirus infection in asymptomatic Peruvian women: a community-based study - del Valle-Mendoza, Juana (2021)
Objective: To determine the general and genotype-specific prevalence of HPV and to identify potential risk factors for the infection in a population-based screening of Peruvian women. Results: A total of 524 samples were analyzed by PCR and a total of 100 HPV positive samples were found, of which 89 were high-risk, 19 were probably oncogenic, 9 were low-risk and 27 other HPV types. The 26–35 and 36–45 age groups showed the highest proportion of HPV positive samples with a total of 37% (37/100) and 30% (30/100), respectively. Moreover, high-risk HPV was found in 33.7% of both groups and probably oncogenic HPV in 52.6% and 31.6%, respectively. High-risk HPV were the most frequent types identified in the population studied, being HPV-52, HPV-31 and HPV-16 the most commonly detected with 17.6%, 15.7% y 12.9%, respectively. Demographic characteristics and habits were assessed in the studied population. A total of 62% high-risk HPV were detected in married/cohabiting women. Women with two children showed the highest proportion (33.8%) of high-risk HPV, followed by women with only one child (26.9%). Those women without history of abortion had a higher frequency of high-risk HPV (71.9%), followed by those with one abortion (25.8%).